2010
DOI: 10.1093/rheumatology/kep407
|View full text |Cite
|
Sign up to set email alerts
|

How to improve DAS28 use in daily clinical practice?--a pilot study of a nurse-led intervention

Abstract: Objectives. To determine whether DAS28 measurements by a specialized nurse, before the rheumatologist visit, in combination with the advice to rheumatologists to reach a DAS28 4 3.2, had beneficial effects on disease activity and medication prescription in patients with RA and to explore possible predictors for variation in medication changes and reasons for non-adherence to the advice to reach a DAS28 4 3.2.Methods. In this pilot study, rheumatologists were randomized to 'usual care' (n = 3) or DAS28 measurem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
47
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(49 citation statements)
references
References 39 publications
1
47
0
Order By: Relevance
“…BehandelStrategieën in Reumatoïde Artritis (BeSt), 26- 55 the TreaTing to Twin Targets (T-4) study, 56,57 the Treatment of Early Aggressive Rheumatoid arthritis (TEAR) trial [58][59][60] and the early rheumatoid arthritis treated with tocilizumab, methotrexate or their combination (U-Act-Early) trial 62 ], three trials 9,50,52,53 examined an established RA population [i.e. British Rheumatoid Outcome Study Group (BROSG) trial, 9 Fransen et al 50 and the Optimisation of Adalimumab study 52,53 ] and two trials 61,63 examined populations that include both patients with early RA and those with established RA [i.e. the TIght COntrol for RA (TICORA) trial 61 examined patients with a disease duration of < 5 years and van Hulst et al 63 reported including both newly diagnosed patients and those with established disease (and did not report on the findings for these patients separately at all)].…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 4 more Smart Citations
“…BehandelStrategieën in Reumatoïde Artritis (BeSt), 26- 55 the TreaTing to Twin Targets (T-4) study, 56,57 the Treatment of Early Aggressive Rheumatoid arthritis (TEAR) trial [58][59][60] and the early rheumatoid arthritis treated with tocilizumab, methotrexate or their combination (U-Act-Early) trial 62 ], three trials 9,50,52,53 examined an established RA population [i.e. British Rheumatoid Outcome Study Group (BROSG) trial, 9 Fransen et al 50 and the Optimisation of Adalimumab study 52,53 ] and two trials 61,63 examined populations that include both patients with early RA and those with established RA [i.e. the TIght COntrol for RA (TICORA) trial 61 examined patients with a disease duration of < 5 years and van Hulst et al 63 reported including both newly diagnosed patients and those with established disease (and did not report on the findings for these patients separately at all)].…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
“…British Rheumatoid Outcome Study Group (BROSG) trial, 9 Fransen et al 50 and the Optimisation of Adalimumab study 52,53 ] and two trials 61,63 examined populations that include both patients with early RA and those with established RA [i.e. the TIght COntrol for RA (TICORA) trial 61 examined patients with a disease duration of < 5 years and van Hulst et al 63 reported including both newly diagnosed patients and those with established disease (and did not report on the findings for these patients separately at all)]. Six studies 50 52,53 the T-4 study 56,57 and the TEAR trial [58][59][60] ) and six studies 26- 54 and the TEAR trial [58][59][60] ).…”
Section: Assessment Of Clinical Effectivenessmentioning
confidence: 99%
See 3 more Smart Citations